Implementasi Pendekatan Teaching at The Right Level (TaRL) Melalui Pembelajaran Berdiferensiasi pada Mata Pelajaran Bahasa Indonesia di SMP Negeri 1 Surakarta - Eko Wahyu Saputro; Ani Rakhmawati; Reni Sunarso (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to elucidate the implementation of the Teaching at The Right Level (TaRL) approach through differentiated learning in the Indonesian language subject at SMP Negeri 1 Surakarta. This study is classified as qualitative descriptive research. The data sources used in this research include the learning process, informants from the Indonesian language teachers at SMP Negeri 1 Surakarta, documents related to Teaching at The Right Level (TaRL) through differentiated learning, as well as field notes on the learning process using the Teaching at The Right Level (TaRL) approach through differentiated learning. Data collection techniques include observation, interviews, and document analysis. The results of this research indicate that the implementation of the Teaching at The Right Level (TaRL) approach through differentiated learning aligns with the stages of the Teaching at The Right Level (TaRL) approach, namely classifying students' learning needs, designing and implementing differentiated learning, and reflecting on and evaluating the learning process.